Characteristics of ZnO-SnO2 Composite Nanofibers as a Photoanode in Dye-Sensitized Solar Cells - Bakr, Zinab H.; Wali, Qamar; Yang, Shengyuan; Yousefsadeh, Maryam; Padmasree, K. P.; Jamil, Ismail; Mohd Hasbi, Ab. Rahim; M. M., Yusoff; Rajan, Jose (American Chemical Society (ACS Publications), 2018)
Composite materials are aimed to combine properties of their components to achieve a desired device functionality; however, synthesizing them in morphologies such as one-dimensional nanofibers is challenging. This article compares optical and electrical properties of ZnO–SnO2 composite nanofibers (CNFs) synthesized by electrospinning technique for energy-harvesting applications with similar CNFs (TiO2–SnO2) and their single-component nanofibers (NFs). The composite formation is confirmed by X-ray and electron diffraction, energy-dispersive X-ray, high-resolution transmission electron microscopy (HRTEM), and X-ray photoelectron spectroscopy analyses; the morphology is examined by HRTEM and field-emission scanning electron microscopy. The electrochemical properties of the CNFs are studied by cyclic voltammetry, absorption spectroscopy, and electrochemical impedance spectroscopy. The CNFs behaved as a single semiconducting material of band gap ∼3.32 (ZnO–SnO2) and ∼3.15 (TiO2–SnO2) eV. The CNFs showed superior photoconversion efficiency (∼5.60% for ZnO–SnO2 and ∼8.0% for TiO2–SnO2 CNFs) compared to its binary counterparts SnO2 (∼3.90%), ZnO (∼1.38%), and TiO2 (∼5.1%) when utilized as photoanodes in dye-sensitized solar cells.